Sexual activity during pregnancy and prognosis of labor in Cameroonian women: a cohort study. (September 2014) - Foumane, Pascal; Mboudou, Emile Telesphore; Sama, Julius Dohbit; Baba, Souley; Enama Mbatsogo, Bernard Armand; Ngwana, Lilian
Abstract Objective: Our aim was to assess the effects of sexual activity during pregnancy on the prognosis of labor. Methods: It was a prospective cohort study of labor comparing 72 women declaring unprotected vaginal sexual intercourse after 37 weeks of pregnancy consecutively recruited to 72 women claiming no sexual contact after 37 weeks of pregnancy also consecutively recruited. Results: The sexually active group at term were significantly involved in more frequent heterosexual intercourse after 28 weeks pregnancy and before term (RR = 37.8; CI = 19.8–515.4). Women sexually active were significantly admitted during the active phase of labor (RR = 2.4; IC = 1.6–5.3), with the fetal head at station 0 and more (RR = 1.5; CI = 1.3-5.2). They significantly had a shorter active phase (RR = 1.7; CI = 1.5–3.7) and a shorter second stage (RR = 1.5; CI = 1.2–3.3). They significantly had a normal pattern of labor (RR = 2.1; CI = 1.2–5.3), a higher rate of spontaneous deliveries (RR = 2.1; CI = 1.5–4.5), a lower rate of caesarean sections (RR = 0.46; CI = 0.1–0.8) and needed less oxytocin usage before expulsion (RR = 0.5; CI = 0.2–0.7). Conclusion: Sexual activity during pregnancy improves the prognosis of labor in Cameroonian women. In the absence of contraindications, consented unprotected heterosexual intercourse should be promoted in pregnant women.